Monitoring and mechanisms of insecticide resistance in Chilo suppressalis (Lepidoptera: Crambidae), with special reference to diamides. Issue 6 (11th November 2016) - Yao, Rong; Zhao, Dan‐Dan; Zhang, Shuai; Zhou, Li‐Qi; Wang, Xin; Gao, Cong‐Fen; Wu, Shun‐Fan
Abstract: BACKGROUND: The rice stem borer, Chilo suppressalis Walker (Lepidoptera: Crambidae), is one of the most economically important pests of rice in Asia. Chemical control remains the most efficient primary means for controlling this pest. RESULTS: Significant variations among field populations in their resistance to seven insecticides were observed. The populations exhibited LC50 values that ranged between 0.605 and 108.088 mg AI L −1 for chlorantraniliprole and between 0.046 and 3.919 mg AI L −1 for flubendiamide. The YY14 population collected from Yuyao in Zhejiang Province in 2014 showed a moderate resistance level to the two diamides, i.e. up to 77.6‐fold and 42.6‐fold for chlorantraniliprole and flubendiamide respectively. Synergism tests and biochemical assays showed no obvious correlations between diamide resistance and three detoxifying enzymes. Sequence comparison of the ryanodine receptor gene between the YY14 resistant population and susceptible population revealed that a glycine to glutamic acid substitution (G4910E) was presented in the YY14 population. CONCLUSION: G4910E mutation might be involved in the resistance evolution of C. suppressalis to the diamides. An appropriate insecticide resistance management programme should be established to maintain the effectiveness of the insecticides and to ensure sustainable management. © 2016 Society of Chemical Industry